Reduction of aggressive behaviour following hypothalamic deep brain stimulation: Involvement of 5-HT1A and testosterone - Flavia Venetucci Gouveia; Mustansir Diwan; Raquel C.R. Martinez; Peter Giacobbe; Nir Lipsman; Clement Hamani (Neurobiology of Disease, 2023)
Background: Aggressive behaviour (AB) may occur in patients with different neuropsychiatric disorders. Although most patients respond to conventional treatments, a small percentage continue to experience AB despite optimized pharmacological management and are considered to be treatment-refractory. For these patients, hypothalamic deep brain stimulation (pHyp-DBS) has been investigated. The hypothalamus is a key structure in the neurocircuitry of AB. An imbalance between serotonin (5-HT) and steroid hormones seems to exacerbate AB. Objectives: To test whether pHyp-DBS reduces aggressive behaviour in mice through mechanisms involving testosterone and 5-HT. Methods: Male mice were housed with females for two weeks. These resident animals become territorial and aggressive towards intruder mice placed in their cages. Residents had electrodes implanted in the pHyp. DBS was administered for 5 h/day for 8 consecutive encounters prior to the interaction with the intruder. After testing, blood and brains were recovered for measuring testosterone and 5-HT receptor density, respectively. In a second experiment, residents received WAY-100635 (5-HT1A antagonist) or saline injections prior to pHyp-DBS. After the first 4 encounters, the injection allocation was crossed, and animals received the alternative treatment during the next 4 encounters. Results: DBS-treated mice showed reduced AB that was correlated with testosterone levels and an increase in 5-HT1A receptor density in the orbitofrontal cortex and amygdala. Pre-treatment with WAY-100635 blocked the anti-aggressive effect of pHyp-DBS. Conclusions: This study shows that pHyp-DBS reduces AB in mice via changes in testosterone and 5-HT1A mechanisms.